Uncertainty in working capital management and firm performance: a COVID-19 perspective - Hossain, Mohammad Reyad; Zariyawati, M. A. (Universiti Putra Malaysia, 2022)
This study examines the impact of the COVID-19 pandemic on firms' working capital management (WCM) and, eventually, firms’ performance of 4513 China and 1049 United Kingdom (UK) publicly listed firms. Static panel data analysis was used to achieve the objective of this study. By using the cash conversion cycle (CCC) as a proxy for WCM, we discover that COVID-19 has a negative effect on the WCM of Chinese firms. We also found a statistically significant negative relationship between WCM and Chinese firms’ performance. This suggests that when firms are affected by COVID-19 uncertainty, Chinese firms will be compelled to reduce their account receivables, inventory levels, and seek increased credit terms from suppliers. Contrary to Chinese firms, we discover the positive relationship between COVID-19 and WCM for UK firms. Further, the relationship between WCM and UK firms’ performance is positively associated. The greater investment in WCM by UK firms during the COVID-19 period generated a higher firm performance.